Composite artificial graphite negative electrode material and preparation method and application thereof
Through the composite technology of large-particle artificial graphite and small-particle artificial graphite, the particle size distribution is regulated, and the problem of low tap density of artificial graphite in the existing technology is solved, achieving efficient performance improvement and cost reduction.
Patent Information
- Application Number
- CN202411940504.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-28
AI Technical Summary
The prior art has problems of low production efficiency and excessively fine particle size in improving the tap density of artificial graphite, which affects its performance in lithium-ion batteries.
By using the composite method of large-particle artificial graphite and small-particle artificial graphite, the particle size distribution is regulated, so that small-particle artificial graphite fills the gap between large-particle artificial graphite, thereby improving the tap density.
It has achieved the improvement of the tap density and cycle life of the negative electrode material of lithium-ion battery, while taking into account the energy density and charging and discharging performance of the secondary battery, reducing production costs.
Smart Images

Figure CN119725527A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion battery negative electrode materials, and specifically relates to a composite artificial graphite negative electrode material and a preparation method and application thereof. Background Art
[0002] Artificial graphite has become the preferred negative electrode active material for lithium-ion batteries due to its good cycle performance and relatively high energy density. Artificial graphite is usually made into negative electrode sheets through processes such as pulping, coating and drying. Therefore, it needs to have good processability during the pulping process so that it can be evenly dispersed in the slurry system. The tap density of artificial graphite directly affects its physical properties and processing properties. Therefore, in order to further improve the processing performance of artificial graphite, it is urgent to significantly increase its tap density.
[0003] The prior art discloses many technical solutions for improving the tap density of artificial graphite. For example, spheroidization can be performed, and the classification points can be further optimized and the fine powder can be removed to improve its tap density, but there is a disadvantage of low production efficiency; or the tap density of artificial graphite can be improved through shaping process and surface modification, including that the tap density can be improved by appropriately extending the shaping time, but too long a shaping time may cause the artificial graphite to be too fine in particle size, which ultimately affects the yield.
[0004] In summary, the above technical solution still has some shortcomings. Therefore, it is very necessary to develop an artificial graphite material with high tap density and good electrochemical properties for application in lithium-ion batteries. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention aims to provide a composite artificial graphite negative electrode material and a preparation method and application thereof. The present invention achieves the purpose of improving the tap density of the product by regulating the composition and particle size distribution of the composite artificial graphite negative electrode material.
[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0007] In the first aspect, the present invention provides a composite artificial graphite negative electrode material, which includes large-particle artificial graphite and small-particle artificial graphite; the particle size distribution of the large-particle artificial graphite satisfies: Dv50>5.0μm, and Dn10>1.0μm; the particle size distribution of the small-particle artificial graphite satisfies: Dv50≤5.0μm, and Dn10≤1.0μm; the small-particle artificial graphite includes primary particles, and the small-particle artificial graphite is derived from the crushed tailings in the preparation process of the large-particle artificial graphite.
[0008] Compared with the use of granular artificial graphite materials with a uniform average particle size, the present invention adopts a method of compounding large-particle artificial graphite crushed main material and small-particle artificial graphite crushed tail material, so that the small-particle artificial graphite fills the gaps between large-particle artificial graphite, thereby narrowing the particle size distribution of the crushed main material. This not only improves the tap density of the product, but also ensures that the composite artificial graphite negative electrode material has a higher specific capacity.
[0009] On the one hand, the large-particle artificial graphite with a larger particle size has a smaller specific surface area, so it has fewer side reactions with the electrolyte, thereby effectively improving the compaction density and coulomb efficiency of the prepared negative electrode sheet. On the other hand, the small-particle artificial graphite with a smaller particle size has more lithium ion migration channels and shorter paths, so its rate performance is better, and due to the addition of small-particle artificial graphite with a smaller particle size, the compaction density of the negative electrode sheet can be further improved to a certain extent. In summary, the present invention can not only improve the compaction density and cycle life of the prepared negative electrode sheet by rationally designing the particle size distribution of the artificial graphite negative electrode material, but also take into account the energy density and charge-discharge performance of the assembled secondary battery. If only a granular artificial graphite material with a single average particle size is used, it is impossible to achieve the excellent performance of the composite use of artificial graphite particles with different particle size distributions, such as high compaction density and long cycle life.
[0010] In addition, the small-particle artificial graphite provided by the present invention is derived from the crushed tailings in the preparation process of large-particle artificial graphite, thereby greatly reducing the production cost of the product and saving raw materials.
[0011] It should be noted that Dv50 represents the particle size corresponding to 50% in the volume distribution of artificial graphite material particles in micrometers; Dn10 represents the particle size corresponding to 10% in the number distribution of artificial graphite material particles in micrometers.
[0012] In the present invention, the particle size distribution of the large-particle artificial graphite satisfies: Dv50>5.0μm, and Dn10>1.0μm, Dv50 can be, for example, 6.0μm, 8.0μm, 10.0μm, 12.0μm, 15.0μm, 18.0μm, 20.0μm, 22.0μm, 25.0μm, etc.; and Dn10 can be, for example, 2.0μm, 3.0μm, 4.0μm, 5.0μm, 6.0μm, 7.0μm, 8.0μm, 9.0μm, 10.0μm, etc.
[0013] In the present invention, the particle size distribution of the small particle artificial graphite satisfies: Dv50≤5.0μm, and Dn10≤1.0μm, Dv50 can be, for example, 1.0μm, 1.2μm, 1.5μm, 1.8μm, 2.0μm, 2.2μm, 2.5μm, 2.8μm, 3.0μm, 3.2μm, 3.5μm, 3.8μm, 4.0μm, 4.2μm, 4.5μm, 4.8μm, 5.0μm, etc.; and Dn10 can be, for example, 0.1μm, 0.2μm, 0.3μm, 0.4μm, 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1.0μm, etc.
[0014] Further preferably, the particle size distribution of the large-particle artificial graphite satisfies: Dv50 is 6 μm-20 μm, and Dn10 is >2.0 μm.
[0015] More preferably, the particle size distribution of the large-particle artificial graphite satisfies: Dv50 is 8 μm-15 μm, and Dn10 is >2.0 μm.
[0016] Further preferably, the particle size distribution of the small-particle artificial graphite satisfies: Dv50 is 3 μm-5 μm, and Dn10 is 0.3 μm-1 μm.
[0017] Preferably, the mass ratio of the large-particle artificial graphite to the small-particle artificial graphite is 100:(5-30), preferably 100:(5-20), for example, it can be 100:5, 100:8, 100:10, 100:12, 100:15, 100:18, 100:20, 100:22, 100:25, 100:28, 100:30, etc. The present invention adjusts the mass ratio of large-particle artificial graphite and small-particle artificial graphite so that the tap density of the composite artificial graphite negative electrode material reaches the maximum value. If the mass ratio of large-particle artificial graphite and small-particle artificial graphite is relatively low, the tap density of the composite artificial graphite negative electrode material will be reduced; if the mass ratio of large-particle artificial graphite and small-particle artificial graphite is relatively high, the tap density of the composite artificial graphite negative electrode material cannot be greatly improved.
[0018] Preferably, the large-particle artificial graphite includes primary particles and / or secondary particles.
[0019] In the present invention, the secondary particles are formed by bonding the primary particles. The particle size distribution of the secondary particle material is narrower, and the dynamic performance is improved, so that the prepared composite artificial graphite negative electrode material has better performance in particle size, tap density and electrochemical performance.
[0020] Preferably, the raw material of the large-particle artificial graphite includes petroleum coke and / or needle coke, and the raw material of the small-particle artificial graphite is the crushed tailings of the raw material of the large-particle artificial graphite.
[0021] Preferably, the particle size Dn10 of the composite artificial graphite negative electrode material is ≥0.7 μm, for example, it can be 0.7 μm, 0.9 μm, 1.0 μm, 2.0 μm, 3.0 μm, 4.0 μm, 5.0 μm, 6.0 μm, 7.0 μm, 8.0 μm, 9.0 μm, etc.
[0022] Preferably, the tap density of the composite artificial graphite negative electrode material is 0.05 g / cm higher than the tap density of the large-particle artificial graphite particles. 3 ~0.15g / cm 3 , for example, it can be 0.05 g / cm 3 , 0.06g / cm 3 , 0.07g / cm 3 , 0.08g / cm 3 , 0.09g / cm 3 , 0.10g / cm 3 , 0.12g / cm 3 , 0.13g / cm 3 , 0.14g / cm 3 , 0.15g / cm 3 wait.
[0023] The present invention further improves the tap density of the composite artificial graphite negative electrode material by blending large and small particles of artificial graphite.
[0024] Preferably, the oil absorption value of the composite artificial graphite negative electrode material is 3ml / 100g to 6ml / 100g lower than the oil absorption value of the large-particle artificial graphite. For example, it can be 3ml / 100g, 3.2ml / 100g, 3.5ml / 100g, 3.8ml / 100g, 4ml / 100g, 4.2ml / 100g, 4.5ml / 100g, 4.8ml / 100g, 5ml / 100g, 5.2ml / 100g, 5.5ml / 100g, 5.8ml / 100g, 6ml / 100g, etc.
[0025] Preferably, in the scanning electron microscope image of the cross section of the pole piece containing the composite artificial graphite negative electrode material, the porosity of any 200μm×150μm cross section without a carrier is less than 20%; preferably, the porosity is ≤16%, for example, it can be 5%, 8%, 10%, 12%, 15%, 16%, 18%, 19%, etc. The present invention adjusts the porosity of the negative electrode sheet so that it can maintain a high tap density. If the porosity of the cross section of the pole piece containing the composite artificial graphite negative electrode material is higher than 20%, the tap density will be reduced.
[0026] The porosity is directly calculated by using ImageJ image analysis software to obtain the pore area and cross-sectional area of the cross section, and the porosity is calculated by the following formula: porosity = (pore area within the cross-sectional area / cross-sectional area) × 100%.
[0027] The electrode sheet is prepared by a wet process, which includes mixing the composite artificial graphite negative electrode material with sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR) and conductive agent Super P in a mass ratio of 94:2:2:2, using copper foil as a carrier, and rolling it using a double-roll pressing equipment MSK-2300A at a pressure of 15 tons.
[0028] In a second aspect, the present invention provides a method for preparing the composite artificial graphite negative electrode material according to the first aspect, the method comprising the following steps:
[0029] (1) providing a raw material of large-particle artificial graphite, crushing the raw material of large-particle artificial graphite to obtain a crushed main material and a crushed tailing, and collecting the crushed tailing with a particle size distribution satisfying Dv50≤5.0μm and Dn10≤1.0μm as the crushed tailing to be processed;
[0030] (2) graphitizing the crushed main material and the crushed tailings to be processed respectively to obtain large-particle artificial graphite and small-particle artificial graphite;
[0031] (3) Mixing the large-particle artificial graphite and the small-particle artificial graphite to obtain the composite artificial graphite negative electrode material.
[0032] Preferably, the raw material of the large-particle artificial graphite in step (1) includes petroleum coke and / or needle coke.
[0033] Preferably, the crushed tailings are used as the crushed tailings to be processed, or the crushed tailings to be processed are obtained by crushing the crushed tailings at least once.
[0034] Preferably, the crushing equipment includes a mechanical mill, a roller mill or a jet mill, and the re-crushing equipment includes a jet mill.
[0035] Further preferably, the crushing equipment is a mechanical mill.
[0036] In the present invention, the crushing is a micron-level crushing process, and the micron-level crushing process also includes a coarse crushing process before the micron-level crushing process.
[0037] Preferably, the particle size distribution of the crushed main material in step (2) satisfies Dv50>5.0μm and Dn10>1.0μm, and the crushed main material is graphitized; and / or the crushed main material is subjected to secondary granulation to obtain a granulated material having a particle size distribution satisfying Dv50>5.0μm and Dn10>1.0μm, and the granulated material is graphitized.
[0038] In the present invention, the secondary granulation process includes heating and granulating the primary particles and the binder.
[0039] In the present invention, the secondary granulation process is a conventional secondary granulation process in the art, and preferably a vertical reactor is used.
[0040] In the present invention, the binder exemplarily includes asphalt.
[0041] Preferably, the temperature of the graphitization treatment in step (2) is 2800°C-3000°C, for example, 2800°C, 2850°C, 2900°C, 2950°C, 3000°C, etc.
[0042] In the present invention, the graphitization treatment equipment exemplarily includes an Acheson furnace.
[0043] Preferably, the graphitization treatment in step (2) further includes a screening treatment.
[0044] In the present invention, the screening equipment exemplarily includes a vibration screening machine or an ultrasonic screening machine.
[0045] Preferably, during the screening process, the mesh size of the sieve is 150-600 mesh, for example, it can be 150 mesh, 270 mesh, 325 mesh, 500 mesh, 600 mesh, etc.
[0046] The preparation method provided by the present invention includes raw material crushing, secondary screening of tailings, graphitization treatment, screening and blending processes in sequence, specifically, firstly collecting the raw material crushing main material and tailings fine powder separately in the crushing stage, thereby narrowing the particle size distribution of the crushing main material, and then the crushing main material and tailings fine powder are respectively subjected to graphitization firing and finished product screening treatment, and finally blended to prepare a composite artificial graphite negative electrode material with a higher tap density. In addition, the present invention reduces production costs and saves raw materials by recycling tailings.
[0047] In a third aspect, the present invention provides a negative electrode sheet, the negative electrode sheet comprising a negative electrode active material, the negative electrode active material comprising the composite artificial graphite negative electrode material according to the first aspect.
[0048] The negative electrode sheet prepared from the composite artificial graphite negative electrode material provided by the present invention has higher volume energy density and longer cycle life.
[0049] In a fourth aspect, the present invention provides a secondary battery, comprising the negative electrode sheet according to the third aspect.
[0050] The secondary battery assembled by the negative electrode sheets provided by the present invention has high energy density, high specific capacity and high coulombic efficiency.
[0051] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0052] Compared with the prior art, the present invention has the following beneficial effects:
[0053] The present invention provides a composite artificial graphite negative electrode material, which is prepared by compounding a large-particle artificial graphite crushed main material and a small-particle artificial graphite crushed tail material so that the small-particle artificial graphite fills the gaps between the large-particle artificial graphite particles, thereby narrowing the particle size distribution of the crushed main material. This not only improves the tap density of the product, but also ensures that the composite artificial graphite negative electrode material has a higher specific capacity.
[0054] On the one hand, large-particle artificial graphite with a larger particle size has a smaller specific surface area, so it has fewer side reactions with the electrolyte, thereby effectively improving the compaction density and coulomb efficiency of the prepared negative electrode sheet. On the other hand, small-particle artificial graphite with a smaller particle size has more lithium ion migration channels and shorter paths, so its rate performance is better, and due to the addition of small-particle artificial graphite with a smaller particle size, the compaction density of the negative electrode sheet can be further improved to a certain extent. In summary, the present invention can not only improve the compaction density and cycle life of the prepared negative electrode sheet by rationally designing the particle size distribution of the artificial graphite negative electrode material, but also take into account the energy density and charge and discharge performance of the assembled secondary battery.
[0055] In addition, the small-particle artificial graphite provided by the present invention is derived from the crushed tailings in the preparation process of large-particle artificial graphite, thereby greatly reducing the production cost of the product and saving raw materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0056] Figure 1This is a scanning electron microscope image of the cross section of the negative electrode sheet prepared from the composite artificial graphite negative electrode material provided in Example 2.
[0057] Figure 2 This is a scanning electron microscope image of the cross section of the negative electrode sheet prepared from the composite artificial graphite negative electrode material provided in Comparative Example 2. DETAILED DESCRIPTION
[0058] The technical solution of the present invention is further described below by combining the accompanying drawings and specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0059] Example 1
[0060] The present embodiment provides a composite artificial graphite negative electrode material, which includes large-particle artificial graphite primary particles and small-particle artificial graphite primary particles, the particle size distribution of the large-particle artificial graphite primary particles satisfies: Dv50 = 9.0 μm, and Dn10 = 1.1 μm, and the particle size distribution of the small-particle artificial graphite primary particles satisfies: Dv50 = 4.0 μm, and Dn10 = 0.3 μm, and the small-particle artificial graphite primary particles are derived from the crushed tailings in the preparation process of the large-particle artificial graphite primary particles. Wherein, the mass ratio of the large-particle artificial graphite primary particles to the small-particle artificial graphite primary particles is 100:10.
[0061] This embodiment also provides a method for preparing the composite artificial graphite negative electrode material, which comprises the following steps:
[0062] (1) Drying the green needle coke and then crushing it, and then mechanically grinding it to a particle size distribution of Dv50 = 9.0 μm and Dn10 = 1.1 μm to obtain the main crushed material, named A1; collecting the fine powder of the crushed tail material and crushing it again to a particle size distribution of Dv50 = 4.0 μm and Dn10 = 0.3 μm, named AS1;
[0063] (2) The crushed main material A1 and the crushed tail fine powder AS1 are graphitized in an Acheson furnace at a temperature of 2800° C., and large-particle artificial graphite primary particles C1 and small-particle artificial graphite primary particles CS1 are obtained after the graphitization.
[0064] (3) The large-particle artificial graphite primary particles C1 and the small-particle artificial graphite primary particles CS1 are sieved respectively, the sieving equipment uses an ultrasonic sieving machine, the sieve uses a 300-mesh sieve, and the corresponding sieved products are named D1 and DS1 respectively;
[0065] (4) The sieved products D1 and DS1 were mixed in a weightless mixer at a mass ratio of 100:10, and after mixing evenly, the composite artificial graphite negative electrode material was obtained, which was named E1.
[0066] Example 2
[0067] The present embodiment provides a composite artificial graphite negative electrode material, which includes large-particle artificial graphite secondary particles and small-particle artificial graphite primary particles obtained by granulating large-particle artificial graphite primary particles, the particle size distribution of the large-particle artificial graphite secondary particles satisfies: Dv50 = 14.3 μm, and Dn10 = 3.6 μm, and the particle size distribution of the small-particle artificial graphite primary particles satisfies: Dv50 = 4.0 μm, and Dn10 = 0.3 μm, and the small-particle artificial graphite primary particles are derived from the crushed tailings in the preparation process of the large-particle artificial graphite primary particles. Wherein, the mass ratio of the large-particle artificial graphite secondary particles to the small-particle artificial graphite primary particles is 100:15.
[0068] This embodiment also provides a method for preparing the composite artificial graphite negative electrode material, which comprises the following steps:
[0069] (1) Dry the green needle coke and then crush it, and then grind it mechanically to obtain a crushed main material with a particle size distribution of Dv50=9.0μm and Dn10=1.1μm, and then obtain A1; perform secondary granulation treatment on A1, specifically, evenly mix A1 and asphalt binder, and heat and granulate them in a vertical kettle to obtain a large-particle artificial graphite secondary particle precursor with a particle size distribution of Dv50=14.3μm and Dn10=3.6μm, and then obtain B2; collect the fine powder of the crushed tail and crush it to Dv50=4.0μm and Dn10=0.3μm for secondary granulation, and then obtain AS1;
[0070] (2) The large-particle artificial graphite secondary particle precursor B2 and the crushed tail fine powder AS1 are graphitized in an Acheson furnace at a temperature of 3000° C., and large-particle artificial graphite secondary particles C2 and small-particle artificial graphite primary particles CS1 are obtained after the graphitization.
[0071] (3) The large-particle artificial graphite secondary particles C2 and the small-particle artificial graphite primary particles CS1 are sieved respectively, the sieving equipment uses an ultrasonic sieving machine, the sieve uses a 300-mesh sieve, and the corresponding sieved products are named D2 and DS1 respectively;
[0072] (4) The sieved products D2 and DS1 were mixed in a weightless mixer at a mass ratio of 100:15, and after mixing evenly, the composite artificial graphite negative electrode material was obtained, which was named E2.
[0073] Example 3
[0074] The present embodiment provides a composite artificial graphite negative electrode material, which includes large-particle artificial graphite primary particles and small-particle artificial graphite primary particles, the particle size distribution of the large-particle artificial graphite primary particles satisfies: Dv50 = 11.2 μm, and Dn10 = 2.4 μm, and the particle size distribution of the small-particle artificial graphite primary particles satisfies: Dv50 = 3.9 μm, and Dn10 = 0.3 μm, and the small-particle artificial graphite primary particles are derived from the crushed tailings in the preparation process of the large-particle artificial graphite primary particles. Wherein, the mass ratio of the large-particle artificial graphite primary particles to the small-particle artificial graphite primary particles is 100:12.
[0075] This embodiment also provides a method for preparing the composite artificial graphite negative electrode material, which comprises the following steps:
[0076] (1) The needle coke calcined coke is dried and then roughly crushed, and then mechanically crushed to a particle size distribution of Dv50 = 11.2 μm and Dn10 = 2.4 μm, to obtain the main crushed material, named A3; the fine powder of the crushed tail is collected and crushed again to Dv50 = 3.9 μm and Dn10 = 0.3 μm, named AS3;
[0077] (2) The crushed main material A3 and the crushed tail fine powder AS3 are graphitized in an Acheson furnace at a temperature of 2900° C. to obtain large-particle artificial graphite primary particles C3 and small-particle artificial graphite primary particles CS3;
[0078] (3) The large-particle artificial graphite primary particles C3 and the small-particle artificial graphite primary particles CS3 are sieved respectively, the sieving equipment uses an ultrasonic sieving machine, the sieve uses a 300-mesh sieve, and the corresponding sieved products are named D3 and DS3 respectively;
[0079] (4) The sieved products D3 and DS3 were mixed in a weightless mixer at a mass ratio of 100:12, and after mixing evenly, the composite artificial graphite negative electrode material was obtained, which was named E3.
[0080] Example 4
[0081] The difference between this embodiment and embodiment 1 is that the mass ratio of large-particle artificial graphite primary particles to small-particle artificial graphite primary particles is 100:1, and the rest is the same as embodiment 1.
[0082] Example 5
[0083] The difference between this embodiment and embodiment 1 is that the mass ratio of large-particle artificial graphite primary particles to small-particle artificial graphite primary particles is 100:35, and the rest is the same as embodiment 1.
[0084] Comparative Example 1
[0085] The difference between this comparative example and Example 1 is that no crushing tailing fine powder AS1 is added, and only one artificial graphite material D1 prepared from the crushing main material A1 is provided, and the rest is the same as Example 1.
[0086] Comparative Example 2
[0087] The difference between this comparative example and Example 2 is that no crushed tailing fine powder AS1 is added, and only one artificial graphite material D2 prepared from a large-particle artificial graphite secondary particle precursor B2 is provided, and the rest is the same as Example 2.
[0088] Comparative Example 3
[0089] The difference between this comparative example and Example 3 is that no crushing tailing fine powder AS3 is added, and only one artificial graphite material D3 prepared from the crushing main material A3 is provided, and the rest is the same as Example 3.
[0090] Comparative Example 4
[0091] The difference between this comparative example and Example 1 is that the particle size distribution of the crushed main material A1 satisfies: Dv50=9.0μm, and Dn10=0.5μm, and the rest is the same as Example 1.
[0092] Performance Testing
[0093] (1) Physical and chemical properties test
[0094] The composite artificial graphite negative electrode materials provided in Examples 1 to 5 and the artificial graphite materials provided in Comparative Examples 1 to 4 were subjected to physical and chemical tests, including particle size distribution, tap density and oil absorption value. The test results are shown in Table 1.
[0095] (2) Porosity of negative electrode sheet
[0096] The composite artificial graphite negative electrode material provided in Examples 1 to 5 and the artificial graphite material, carboxymethyl cellulose, styrene-butadiene rubber and conductive agent Super P provided in Comparative Examples 1 to 4 were slurried in a mass ratio of 94:2:2:2 to obtain a negative electrode slurry, and then the negative electrode slurry was scraped on a copper foil, and the MSK-2300A roller pressing equipment was used to roll-form under a pressure of 15 tons, and the negative electrode sheet was obtained after drying. The thickness of the negative electrode sheet without the carrier was about 250μm. The porosity of the negative electrode sheet was analyzed and processed by using the scanning electron microscope image of its cross section using image analysis software (ImageJ), and the following formula was used for calculation: Porosity = (pore area in the cross-sectional area of the negative electrode sheet / cross-sectional area) × 100%, and the test results are shown in Table 2.
[0097] It can be calculated that the porosity of any cross section (size 200×150 μm) in Example 2 is 16%, and the porosity of any cross section (size 200×150 μm) in Comparative Example 2 is 33%. Figure 1 and Figure 2 It can be seen that the gaps between the artificial graphite particles in the composite negative electrode material provided in Example 2 are significantly smaller, which further shows that the present invention can further improve the tap density of the product while ensuring that the composite negative electrode material has a high capacity by narrowing the particle size distribution of large-particle artificial graphite and blending small-particle artificial graphite in the subsequent process.
[0098] (3) Charge and discharge test
[0099] The negative electrode sheet, lithium metal sheet, polypropylene diaphragm and electrolyte prepared from the composite artificial graphite negative electrode material provided in the above-mentioned Examples 1 to 5 and the artificial graphite material provided in Comparative Examples 1 to 4 were made into a lithium ion battery, wherein the electrolyte used was a Zhuhai Saiwei Digital electrolyte. The test conditions of the lithium ion battery are: discharge to 0.005V at a constant current of 0.6mA, stand for 10min, then discharge to 0.005V at a constant current of 0.3mA, stand for 10min, and finally charge to 2.000V at a constant current of 0.6mA, and end the test. The test results are shown in Table 2.
[0100] The test results are shown in Table 1-Table 2:
[0101] Table 1
[0102]
[0103]
[0104] Table 2
[0105]
[0106] It can be seen from Tables 1 and 2 that the present invention adopts a method of compounding large-particle artificial graphite crushed main material and small-particle artificial graphite crushed tail material so that the small-particle artificial graphite fills the gaps between large-particle artificial graphite, thereby narrowing the particle size distribution of the crushed main material. This not only improves the tap density of the product, but also ensures that the composite artificial graphite negative electrode material has a higher specific capacity and first coulomb efficiency.
[0107] Compared with Example 1, Examples 4 and 5 show that the present invention adjusts the mass ratio of large-particle artificial graphite to small-particle artificial graphite so that the tap density of the composite artificial graphite negative electrode material reaches the maximum value. At the same time, the prepared negative electrode sheet also has a higher specific capacity and first coulombic efficiency.
[0108] Compared with Example 1, Comparative Examples 1 to 3 are cases where small particles of artificial graphite are not added, resulting in the obtained artificial graphite negative electrode materials having a lower tap density.
[0109] Compared with Example 1, Comparative Example 4 is a case where Dn10 is lower in the particle size distribution of the crushed main material A1, indicating that the composite artificial graphite material prepared thereby has a lower tap density, and the negative electrode sheet prepared thereby has a lower specific capacity and first coulombic efficiency.
[0110] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A composite artificial graphite negative electrode material, characterized in that: The composite artificial graphite negative electrode material comprises large-particle artificial graphite and small-particle artificial graphite; The particle size distribution of the large-particle artificial graphite satisfies: Dv50>5.0 μm, and Dn10>1.0 μm; The particle size distribution of the small-particle artificial graphite satisfies: Dv50≤5.0μm, and Dn10≤1.0μm; The small-particle artificial graphite includes primary particles, and the small-particle artificial graphite is derived from crushed tailings in the preparation process of the large-particle artificial graphite.
2. The composite artificial graphite negative electrode material according to claim 1, characterized in that: The particle size distribution of the large-particle artificial graphite satisfies: Dv50 is 6 μm-20 μm, and Dn10 is >2.0 μm, and more preferably Dv50 is 8 μm-15 μm, and Dn10 is >2.0 μm; The particle size distribution of the small-particle artificial graphite satisfies: Dv50 is 3 μm-5 μm, and Dn10 is 0.3 μm-1 μm.
3. The composite artificial graphite negative electrode material according to claim 1 or 2, characterized in that: The mass ratio of the large-particle artificial graphite to the small-particle artificial graphite is 100:(5-30), preferably 100:(5-20); And / or, the large-particle artificial graphite includes primary particles and / or secondary particles; And / or, the raw material of the large-particle artificial graphite includes petroleum coke and / or needle coke, and the raw material of the small-particle artificial graphite is the crushed tailings of the raw material of the large-particle artificial graphite.
4. The composite artificial graphite negative electrode material according to any one of claims 1 to 3, characterized in that: The particle size Dn10 of the composite artificial graphite negative electrode material is ≥ 0.7 μm; And / or, the tap density of the composite artificial graphite negative electrode material is 0.05 g / cm higher than the tap density of the large-particle artificial graphite 3 ~0.15g / cm 3 ; And / or, the oil absorption value of the composite artificial graphite negative electrode material is 3 ml / 100 g to 6 ml / 100 g lower than the oil absorption value of the large-particle artificial graphite.
5. The composite artificial graphite negative electrode material according to any one of claims 1 to 4, characterized in that: In the scanning electron microscope image of the cross section of the electrode piece containing the composite artificial graphite negative electrode material, the porosity of any 200 μm×150 μm cross section without the carrier is less than 20%; preferably, the porosity is ≤16%; The porosity was directly calculated by using ImageJ image analysis software to obtain the pore area and cross-sectional area of the cross section, and the porosity was calculated by the following formula: porosity = (pore area within the cross-sectional area / cross-sectional area) × 100%; The electrode sheet is prepared by a wet process, which includes mixing the composite artificial graphite negative electrode material with sodium carboxymethyl cellulose, styrene-butadiene rubber and conductive agent Super P in a mass ratio of 94:2:2:2, using copper foil as a carrier, and rolling it using a double-roll pressing equipment MSK-2300A under a pressure of 15 tons.
6. A method for preparing the composite artificial graphite negative electrode material according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: (1) providing a raw material of large-particle artificial graphite, crushing the raw material of large-particle artificial graphite to obtain a crushed main material and a crushed tailing, and collecting the crushed tailing with a particle size distribution satisfying Dv50≤5.0μm and Dn10≤1.0μm as the crushed tailing to be processed; (2) graphitizing the crushed main material and the crushed tailings to be processed respectively to obtain large-particle artificial graphite and small-particle artificial graphite; (3) Mixing the large-particle artificial graphite and the small-particle artificial graphite to obtain the composite artificial graphite negative electrode material.
7. The method according to claim 6, characterized in that The raw material of the large-particle artificial graphite in step (1) includes petroleum coke and / or needle coke; and / or, using the crushed tailings as the crushed tailings to be processed, or obtaining the crushed tailings to be processed by crushing the crushed tailings at least once; And / or, the crushing equipment includes a mechanical mill, a roller mill or a jet mill, and the re-crushing equipment includes a jet mill.
8. The method according to claim 6 or 7, characterized in that: In step (2), the particle size distribution of the crushed main material satisfies Dv50>5.0μm and Dn10>1.0μm, and the crushed main material is graphitized; and / or the crushed main material is subjected to secondary granulation to obtain a granulated material having a particle size distribution satisfying Dv50>5.0μm and Dn10>1.0μm, and the granulated material is graphitized; And / or, the temperature of the graphitization treatment in step (2) is 2800° C.-3000° C.; And / or, after the graphitization treatment in step (2) is completed, a screening treatment is also included; And / or, the mesh size of the sieve during the screening process is 150-600 mesh.
9. A negative electrode sheet, characterized in that: The negative electrode sheet comprises a negative electrode active material, and the negative electrode active material comprises the composite artificial graphite negative electrode material according to any one of claims 1-5.
10. A secondary battery, characterized in that: The secondary battery includes the negative electrode sheet according to claim 9.